Propuesta metodológica para la optimización de la gestión de proyectos de estructuras metálicas mediante la integración de Lean Construction y PMBOK - Gil, Mary Luz (2025)
This research focuses on the pursuit of optimization in the field of project management for construction with steel structures, integrating the principles of the PMBOK guide and the LEAN methodology. The main objective is to define a process map that represents a flow in process management. To achieve this, a process map is created to describe the conventional management of this type of construction projects, based on literature found in scientific articles as well as the 1999 AISC Project Manager publication. Subsequently, the integration of the 12 knowledge areas and the 5 process groups of PMBOK is identified. Finally, by evaluating the advantages of the LEAN philosophy in construction, a final process map is adjusted. This analysis highlights the absence of key deliverables in project management within the conventional flow, as well as the need to differentiate between the manufacturing and assembly phases due to their different paces and resources. Additionally, through a case study, a numerical approximation is conducted, identifying opportunities to implement the LEAN methodology and improve waste reduction. This study emphasizes the importance of continuous planning and constant monitoring to minimize the waste of material and human resources. It also enables a more compact flow, providing greater transparency in the management of each project phase.